The Central Powers in Russia's Great War and Revolution, 1914-22 : Enemy Visions and Encounters - Sencer, Emre; Perry, Heather R.; Deák, John (John David) (Book collections on Project MUSE., 2020)
"This multiauthor collection of essays analyzes Russia's Great War and Revolution from the perspective of the Central Powers and their encounters with Russia and the Revolution. The peoples of the Central Powers, from elites to civilians, understood the violent clash of armies in a variety of ways. Essays highlight the variety of military and civilian experiences and deal with topics of how soldiers, civilians, and intellectuals perceived Russia and how these understandings translated into security goals, utopian plans for conquered territories, and interethnic violence."--